Photoluminescence and light scattering in lead tungstate single crystals - Tsapenko, A.B.; Tsapenko, B.P.; Bondar, V.G.; Grinyov, B.V.; Pirogov, E.N.; Ryzhikov, V.D. (Functional Materials, 2005)
Temperature dependences of photoluminescence have been obtained for lead tungstate single crystals with stored light sum. The thermal decay effect on the photoluminescence intensity has been revealed, this effect being connected with the pair recombination interaction of the emission centers and electron traps localized in the surrounding thereof. Oscillations in the light reflection intensity have been found near 200 К. Those are supposed to be associated with the action of thermal fluctuations. Отримано температурнi залежностi фотолюмiнесценцiї монокристалiв вольфрамату свинцю з накопиченою свiтлосумою. Виявлено вплив термовисвiчування на iнтенсивнiсть фотолюмiнесценцiї, пов'язаний з парною рекомбiнацiйною взаемодiєю центрiв свiтiння та електронних пасток, локалiзованих у iхньому оточеннi. Виявлено осциляцii iнтенсивностi вiдбивання свiтла в областi 200 К. Припускається iх зв'язок з дiєю теплових флуктуацiй. Получены температурные зависимости фотолюминесценции монокристаллов вольфрамата свинца с накопленной светосуммой. Обнаружено влияние термовысвечивания на интенсивность фотолюминесценции, связанное с парным рекомбинационным взаимодействием центров свечения и электронных ловушек, локализованных в их окружении. Обнаружены осцилляции интенсивности отражения света в области 200 К. Предполагается связь с действием тепловых флуктуаций.